The Effect of Social Media Marketing on Purchase Intention Through Brand Image and Brand Trust as Mediating Variables in Local Bandung Clothing - Trully Mulyadi; Zulganef Zulganef (Dinasti Review, 2025)
This study aims to examine the effect of Social Media Marketing (SMM) on Purchase Intention through Brand Image and Brand Trust as mediating variables for the clothing brand “Take A Chill Pill” (TACP). Although the level of interaction on TACP's Instagram is high, sales conversion is not yet optimal. Using quantitative methods and Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis on 247 Instagram followers of @take___chillpill, the results show that SMM has a significant positive effect on Brand Image (β=0.544) and Brand Trust (β=0.599). Brand Trust has the strongest influence on Purchase Intention (β=0.425), followed by Brand Image (β=0.146), while the direct influence of SMM on Purchase Intention is also significant (β=0.270). The model explains 54.5% of the variance in Purchase Intention with a Goodness of Fit of 0.534. These findings emphasize the importance of building trust and brand image through effective social media marketing strategies to increase consumer purchase intention. This study provides practical guidance for fashion businesses in maximizing the potential of Instagram as a digital marketing platform in Indonesia.